(untitled) - FAO (Rome, 1999)
The committee stresses the increasingly important role of inland capture fisheries and aquaculture in fish production and human nutrition. In this regard, it empasized the benefits of integrades resources management, the need to combat adverse impacts on the environment and for enhanced cooperation between fishers, government agencies and other stakeholders. The committee considered Version 2.0 of FAO's Strategic Framwork ( 2000-20015)
Keywords: fisheries